The Prediction of the Interaction Genistein and Daidzein Compounds on ESR2 Expression by Molecular Docking - Quratul Akyuni; Dwi Hilda Putri; Yuni Ahda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Aims: Estrogen is known to have various roles in the body. ESR2 is an estrogen receptor expressing estrogen receptor beta (ERβ). ERβ is expressed in normal breast epithelial cells as well as in various other tissues such as the uterus, ovary, prostate and brain, and breast cancer cells. One plant that is thought to have the potential to increase ERβ expression is soybean (Glycine max). Soybean plants contain very important phytochemicals, so they are widely used in the food industry as supplements and included in drug formulations. Methods: This type of research is descriptive research conducted using in silico method through the molecular docking approach. The metabolites used were genistein and daidzein for the target protein ESR 2 (PDB ID: 1QKM). Result: The docking results showed that the binding affinity value of the metabolites genistein, daidzein, and native ligand was -9.7 kcal/mol. The RMSD value obtained from LigRMSD was 0.40 with very similar visualization between the ligand test before and after docking. Main Conclusion: The conclusion of this study is that the metabolites of genistein and daidzein are predicted to have the ability to increase ESR2 expression in the human body.